Label-free assessment of preimplantation embryo quality by the Fluorescence Lifetime Imaging Microscopy (FLIM)-phasor approach. (April 2019) - Cho, Ken WY.; Ma, Ning; de Mochel, Nabora Reyes; Pham, Paula Duyen Anh; Yoo, Tae Yeon; Digman, Michelle A.
Abstract : Introduction: The standard non-invasive method to assess embryo quality and viabilityrelies on the visual inspection of embryo morphology according to predefined criteria. Development of more quantitative and objective means for assessing embryo qualitythat are simpler, safer, and faster could provide significant advantages in assistedreproduction. We have applied the phasor-FLIM (Fluorescence Lifetime Imaging Microscopy) approach to preimplantation mouse embryos. FLIM produces an imagebased on the differences in the exponential decay rate of the fluorescence from afluorescent sample. We apply non- invasive phasor-FLIM to identify endogenousfluorescent biomarkers (metabolic signatures) of preimplantation embryos for embryoquality assessment. Material and Methods: Fluorescent lifetimes of endogenous fluorescent species arecollected at various stages of preimplantation development. At each developmentalstage, the mouse embryo displays a characteristic phasor-FLIM signature. Collectively, these signatures define a unique graphical metabolic trajectory (defined as D-trajectory), indicating the dynamic metabolic states of embryos during preimplantationdevelopment. We test whether the major components responsible for the shifts in the Dtrajectoryis intracellular NADH changes by altering its energy metabolism. Second, wedetermine the optimum laser power to examine the effect on the developmentalprogression of embryos until the blastocyst stage. Third, we test whether the uniquelifetime distribution patterns of an embryo cultured under altered physiological statescan be detected by the changes in spectroscopic distributions of phasor-FLIM. Lastly, we define an EVI (Embryo Viability Index) to distinguish preimplantation embryo qualityusing the Distance analysis (DA) program. Results: We have defined a unique graphical metabolic trajectory that correlates with energy metabolism and embryo development. The intrinsic lifetime trajectory of preimplantation embryos cultured in nutrient-compromised media deviates from the normal lifetime distribution, demonstrating that the lifetime trajectory can detect metabolic changes in developing embryos. Lastly, we have identified a combination of mathematical parameters that are statistically different between healthy and unhealthy preimplantation embryos based on machine learning information. The phasor-FLIM approach identifies healthy embryos at the early compaction stage with over 85% accuracy. Conclusions: The phasor-FLIM approach provides an objective, non-invasive, and quantitative method to assess the quality of preimplantation mammalian embryos. Our future goal is to apply the technology for the reproductive biology of human and other mammals.